2015
DOI: 10.1519/jpt.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Determinants of Ongoing Participation in EnhanceFitness

Abstract: Background and Purpose Physical activity has many benefits for older adults, but adherence is often low. The purposes of this study were to: 1) identify motivators and barriers for participation in EnhanceFitness (EF), a group-based exercise program; and 2) quantitatively examine the association between motivators, barriers and individual characteristics, and ongoing participation in the program. Methods This was a prospective, cross-sectional study. We mailed a pilot, investigator-developed survey to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…However, it is important to consider factors that prevent PA in older adults. A common barrier to PA cited in previous studies (Bethancourt et al, 2014;Gillette, Petrescu-Prahova, Herting, & Belza, 2015;Stone & Baker, 2017) and also found here is that patients face physical limitations that prevent them from engaging in PA. Cost and lack of transportation are tangible barriers to PA program participation described by interviewed PTs and in previous studies (Bethancourt et al, 2014;Schutzer & Graves, 2004).…”
Section: Discussionsupporting
confidence: 56%
“…However, it is important to consider factors that prevent PA in older adults. A common barrier to PA cited in previous studies (Bethancourt et al, 2014;Gillette, Petrescu-Prahova, Herting, & Belza, 2015;Stone & Baker, 2017) and also found here is that patients face physical limitations that prevent them from engaging in PA. Cost and lack of transportation are tangible barriers to PA program participation described by interviewed PTs and in previous studies (Bethancourt et al, 2014;Schutzer & Graves, 2004).…”
Section: Discussionsupporting
confidence: 56%
“…Develop and implement a payment model to finance the delivery of evidence-based physical activity programs Use a prospective analysis method (including the frequency, durability, and/or intensity of a specific intervention) to determine impact on health outcomes, costs, and resource utilization Develop a compelling business case for the direct funding of community-based wellness and prevention programs easy or too hard. 23 EF participants reported physical, social, and functional benefits, improved self-image, and a greater sense of well-being. 24 They valued the practical application of class exercises to daily activities that improved quality of life and supported independent living, such as lifting objects and completing household chores.…”
Section: Recommendation Reachmentioning
confidence: 93%
“…Three studies reported determinants of ongoing participation and benefits of program participation, which promote maintenance at the individual level. [22][23][24] Personal motivators for ongoing participation included exercising with others, an accountability-promoting routine, and anticipated health benefits, whereas barriers included not being motivated or ready, experiencing pain while exercising, and having poor general health. 22,23 Program-specific motivators included cost and location of the program 22 ; barriers included class being too…”
Section: Individual-level Maintenancementioning
confidence: 99%
“…Therefore, it is possible to note the increase in demand for physical exercise practices, encouraged by the knowledge of the practical benefits and importance of maintaining independence [25]. However, after initiating physical exercise, many older adults end up not continuing the practice, which reflects in low adherence to the proposed programs [7,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…There are many reasons that induce older adults to abandon the practice of physical exercises, among them, their own health problems [7,25,27,28], death or family health problems [14,28], feeling old or needing rest [29], the negative perception of the effect of physical exercise on the body, such as pain and tiredness [7,27,28], lack of appropriateness of the exercise to the limitations and abilities of the older adults [27,28], and lack of companionship to carry them out [25], in addition to simply not liking to practice exercises [27]. However, studies that address the theme of dropout from the practice of physical exercise are still scarce [7, 25 -28] and the majority have restricted samples, which sometimes undermines their methodological quality.…”
Section: Introductionmentioning
confidence: 99%